The InChildHealth Walkthrough Survey: towards a standardized characterization of classrooms for indoor air quality studies in Europe - Vorkamp, Katrin (2024)
The Horizon Europe project InChildHealth aims to study indoor air quality in European schools and the effects of physical, chemical, and microbiological parameters on the health of school children aged 6-13. As European schools can vary considerably in terms of size, age, materials, equipment, heating, ventilation and air conditioning (HVAC), cleaning procedures, etc., a questionnaire was developed for a standardized description of classrooms and schools. It includes 86 mandatory and 82 optional questions, targeting building characteristics and potential sources of exposure to particles, chemicals, and microorganisms. The survey has been implemented digitally with the option of paper-based versions and future data sharing for combined data interpretation. The project foresees the possibility of revisions based on lessons learned from the application in seven European cities. The final version can be adjusted to other microenvironments and used in future indoor air studies in Europe and elsewhere.